Pengaruh Social Media Marketing , Brand Image, dan Brand Trust Terhadap Brand Loyalty Produk Skintific: (Studi Pada Followers Tiktok @skintific_id) - Firdaus, Labibah Izzati; Andarini, Sonja (JURNAL ADMINISTRASI BISNIS (JAB), 2024)
This research aims to identify and determine the influence of social media marketing, brand image, and brand trust on brand loyalty for skintific products (Study on TikTok Followers @skintific_id). This research method is quantitative, using a questionnaire distributed to 150 respondents. The population in this study are TikTok users who follow the @skintific_id account using a purposive sampling method. The data analysis method used is multiple linear regression. The results of this research are 1) Social media marketing, brand image, and brand trust simultaneously influence brand loyalty for skintific products. 2) Social media marketing partially has a positive and significant effect on brand loyalty for skintific products. 3) Brand image partially has a positive and significant effect on brand loyalty of skintific products. 4) Brand trust partially has a positive and significant effect on brand loyalty for skintific products.